An identification of the soft polyelectrolyte gel-like layer on silica colloids using atomic force and electron microscopy - Škvarla, Jiří; Škvarla, Juraj (Ultramicroscopy, 2017)
A procedure is introduced for measuring the radius of spherical colloid particles from the curvature of upper parts of their central cross-sectional profiles obtained by atomic force microscopy (AFM). To minimize the possible compression and displacement of the spheres, AFM is operated in a mode rendering a constant ultralow pN force on the tip. The procedure allows us to evaluate the mean radius of nearly monodisperse submicrometer spheres of silica in their natively hydrated state in aqueous electrolyte solutions, irrespective of whether they are coagulated or not. A variation in the volume (swelling degree) of layers delimited by the AFM mean radii of these spheres in KCl solutions and their invariable mean radius in vacuum is obtained that follows a scaling power law derived in polymer physics for swellable polyelectrolyte gels and deduced previously by us from coagulation tests. This supports our former suggestion about the existence of soft polyelectrolyte gel-like layer developed spontaneously around silica surfaces and colloids. We discuss this finding in the context of recent knowledge about the structure of the silica/water interface obtained from direct surface force measurements between macroscopic silica surfaces and from particle size measurements of silica colloids and highlight its importance for colloid chemistry and condensed mattter physics.